Utilizing smartphone-based Pinterest applications in developing EFL students speaking skills in Indonesia - Muthmainnah, Muthmainnah; Marzuki, Abdul Gafur; Santiana , Santiana; Erizar, Erizar; Nursyam, Nursyam (Universitas Muhammadiyah Sidoarjo, 2022)
This study raises the issue of how to improve speaking skills using the smartphone-based Pinterest application for second-semester students. The purpose of this study was to determine the improvement of speaking skills using the smartphone-based Pinterest application for second-semester students. The type of research used in this research is Classroom Action Research (CAR). The research subjects are second-semester students. The research instruments are an observation sheet and a performance test sheet. The data analysis technique used is the descriptive statistical technique. The results of the study on second-semester students, experienced a good increase from the learning outcomes of the first cycle to the second cycle, with the standard value of student learning mastery of 85 classical standards. The average value in the first cycle is 48.00 with the level of completeness of learning outcomes in the first cycle of 10% and 90% incomplete. While the learning outcomes in the second cycle with an average value of 85.46 with the completeness level of learning outcomes in the second cycle of 96%, this figure indicates that the average value of the first cycle and the second cycle has increased so that the smartphone-based Pinterest application in improving speaking skills can improve student learning outcomes. HIGHLIGHTS: Student skills in terms of pressure on speechreading and host script reading have gone up by 2.03; Student skills in terms of grammatical aspects have gone up by 2.2; Students' speaking skills in terms of vocabulary have gone up by 2.04;